Determinants of Employees’ Job Satisfaction: A Study of Banking Industries in Sri Lanka - Velnampy, T.; Sivesan, S. (My University, 2012)
The last couple of decades have shown an increase in the study of job satisfaction in relation to organizational outcomes, particularly in management literature. Job satisfaction is a general attitude which is the result of many specific attitudes. Data was collected through seven points Likert type summated rating scales of questionnaires from strongly disagree (1) to strongly agree (7) were adopted to identify indicators. Sophisticated statistical model as “Exploratory Factor Analysis (EFA) has been employed. The results shown factors extract from the analysis that together accounted 84.924% of the total variance. These factors were categorized as payment, achievement and proud to work.